Pacific patterns: Hoa in binary relationships, repetition, symmetry, kupesi, and mana - ’Ō. Ka’ili, Tēvita (Interstices: Journal of Architecture and Related Arts, 2017)
2017 Interstices Under Construction Symposium: Pattern / Surface a pursuit of material narratives. 2nd - 4th June, Auckland University of Technology.